Minyak Biji Nyamplung (Calophyllum inophyllum) Dengan Etanol - Rezki, Rezki; Musta, Rustam; Haetami, Aceng (Indonesian Journal of Chemical Research, 2017)
A study has been conducted on the transesterification of Calophyllum innophyllum seed oil with ethanol. The purpose of this research is to determine the comparison of concentration of phosphoric acid used to remove the gum on the oil, ester content is produced in the process of transesterification with ethanol, the ester yield obtained after the final stage of the transesterification process, the viscosity of the biodiesel produced, moisture content of biodiesel is produced, and density of biodiesel was produced. This research is taken based on consideration production biodiesel by direct transesterification process. Based on research result of good phosphoric acid concentration used to remove oil gum is 85%, volume of biodiesel produced at transesterification equal to 150 mL with yield 80,89%, biodiesel quality parameter measured that viscosity = 0,05 mm2 / s not fulfill Indonesian National Standart (INS), moisture content = 0.045 meets the INS and the density = 0.881 g / cm3 meets the INS